Psoriasis. Diagnostic and therapeutic recommendations of the Polish Dermatological Society. Part II: Moderate to severe psoriasis - Reich, Adam; Szepietowski, Jacek; Adamski, Zygmunt; Chodorowska, Grażyna; Kaszuba, Andrzej; Krasowska, Dorota; Lesiak, Aleksandra; Maj, Joanna; Narbutt, Joanna; Osmola-Mańkowska, Agnieszka; Owczarczyk-Saczonek, Agnieszka; Owczarek, Witold; et al. (Dermatology Review/Przegląd Dermatologiczny, 2018)
The second part of diagnostic and therapeutic guidelines of Polish Dermatological Society focuses on moderate and severe psoriasis, in which phototherapy or systemic treatment should be initiated. Currently, it is recommended to treat moderate to severe plaque psoriasis with either classic anti-psoriatic drugs (methotrexate, cyclosporine, acitretin), TNF--inhibitors (adalimumab, etanercept, infliximab), interleukin 12/23 blocking agent (ustekinumab) and new drugs – interleukin-17 inhibitors (secukinumab, ixekizumab) or interleukin 23 inhibitors (guselkumab, tildrakizumab), as well as the new low-molecular weight agents (apremilast, dimethyl fumarate). In some patients, UV-based therapy may be advisable. These recommendations summarize the principles of the use of these agents in patients with psoriasis in dermatological practice. The efficacy and safety of therapy is discussed and available methods to prevent adverse events are summarized.